Clinical features of indurative mastitis caused by caprine arthritis encephalitis virus - Gregory, Lilian; Birgel Junior , Eduardo H.; Lara , Maria C. C. S. H.; Angelini , Marcelo; Araújo , Wanderley P; Rizzo , Huber; Maiorka , Paulo C.; Castro , Roberto S.; Kiraly , Ana C. M.; Benesi , Fernando J.; Birgel, Eduardo H. (Brazilian Journal of Veterinary Pathology, 2009)
Forty seven mammary glands affected by indurative mastitis were analyzed in order to study parenchyma alterations caused by caprine arthritis encephalitis virus. The study was based on physical examination of the animals and physical-chemical characteristics of the milk. Diagnosis was based on physical examination, serological results, PCR of the milk and histopathology from the mammary tissue. Physical examination showed that indurative process affected the parenchyma of all animals. In many cases, there were nodules of different sizes. PCR detected the virus in the parenchyma and milk of many animals showing that mastitis was caused by a virus. Only 2.35% (47/2000) of the glands evaluated showed consistency alterations related to the virus. PH, chloride content and electroconductivity, as well as somatic cells counts, were greater in animals infected by CAE virus. Alterations in the consistency of the mammary parenchyma were observed in the 25 animals infected. Diameter of the nodules in the parenchyma of eight glands ranged from 1 to 3 cm. Retromammary lymphnodes were enlarged in 4 of 47 glands (8.5%). No clumps were observed in milk samples, but secretion had an aqueous appearance. From the 34 milk samples analyzed, 18/34 (52.9%) showed normal physical-chemical parameters; 9 showed one or two abnormal parameters, and 7 showed 3 or more abnormal parameters.